Thoracic aortic aneurysm combined with intracranial vascular abnormalities caused by dual mutations in MYLK and FBN2: a case report - Cai, Maorong; Liu, Yang; Liao, Zhaodi; Wu, Yiping; Jiao, Jiantong (Frontiers in Genetics, 2025)
ObjectiveTo perform genetic testing on a patient with ruptured vertebral artery aneurysm and subarachnoid hemorrhage who was also found to have a thoracic aortic aneurysm/dissection (TAA/D) during preoperative evaluation, along with their family members. The aim was to identify potential pathogenic gene variants, analyze the inheritance pattern, and investigate the association with coexisting intracranial and aortic vascular abnormalities.MethodsIntracranial vascular lesions (ruptured vertebral artery aneurysm and subarachnoid hemorrhage) were confirmed via computed tomography (CT), computed tomography angiography (CTA), and digital subtraction angiography (DSA). Whole-exome sequencing (WES) via next-generation sequencing (NGS) was conducted on the proband and family members to identify pathogenic gene mutations associated with thoracic aortic aneurysm/dissection (TAA/D) and intracranial vascular abnormalities, thereby elucidating the underlying genetic mechanisms.ResultsThis study reports the management of a patient with a ruptured vertebral artery aneurysm, subarachnoid hemorrhage, and concomitant TAA/D incidentally detected during preoperative evaluation. Imaging studies demonstrated occlusion at the vertebral-basilar junction, with the basilar artery being perfused by the anterior circulation. An aneurysm was identified at the vertebral artery confluence, and the right vertebral artery was found to supply the left vertebral artery, left subclavian artery, and descending aorta. The surgical procedure was performed successfully under general anesthesia, and the patient was transferred to the ward in stable condition. NGS revealed two heterozygous mutations in the patient: a maternally inherited MYLK variant (NM_053025.4): c.834_835insGTA (p.Val278dup) and a paternally inherited FBN2 variant (NM_001999.4): c.1478A>G (p.Gln493Arg). Sequence analysis identified novel mutation sites within both genes, which may contribute to the patient’s combined vascular phenotype. Following the procedure, the patient maintained hemodynamic stability and recovered well after discharge without notable cardiopulmonary abnormalities or surgery-related complications.ConclusionOur findings expand the mutational spectrum of non-syndromic familial thoracic aortic aneurysm/dissection (TAA/D), highlighting that associated gene mutations may also predispose to intracranial vascular abnormalities. We therefore recommend routine intracranial vascular screening (e.g., CTA/DSA) for patients with familial TAA/D to detect potential intracranial lesions. This case underscores the critical need for comprehensive clinical-genetic evaluation to facilitate early diagnosis and timely intervention, which may improve patient outcomes and reduce morbidity.